2020
DOI: 10.1177/2192568220941448
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Short Length of Stay After Long Fusions for Adult Spinal Deformity: Initial Steps Toward Developing an Enhanced Recovery Pathway

Abstract: Study Design: Retrospective cohort study. Objectives: The identification of case types and institutional factors associated with reduced length of stay (LOS) is a key initial step to inform the creation of clinical care pathways that can assist hospitals to maximize the benefit of value-based payment models. The objective of this study was to identify preoperative, intraoperative, and postoperative factors associated with shorter than expected LOS after adult spinal deformity (ASD) surgery. Methods: A retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This could be explained by the fact that ASD patients with the most severe deformity or clinical presentation could have been prioritized during the pandemic. Although our study rigorously controlled for various factors that have been shown to influence LOS and discharge disposition such as age, ASA class, the number of levels fused, revision surgery, and three-column osteotomy, 10 , 29 our analysis did not control for spinal alignment or preoperative health-related quality of life (HRQoL) scores.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that ASD patients with the most severe deformity or clinical presentation could have been prioritized during the pandemic. Although our study rigorously controlled for various factors that have been shown to influence LOS and discharge disposition such as age, ASA class, the number of levels fused, revision surgery, and three-column osteotomy, 10 , 29 our analysis did not control for spinal alignment or preoperative health-related quality of life (HRQoL) scores.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 15 years, many efforts have been made to decrease LOS while ensuring high-quality care for patients via clinical care pathways [ 9 ]. Many studies have reported on factors associated with increased LOS [ 1 , 6 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presurgical physiotherapy, so-called «prehabilitation», has not yet been shown to impact postoperative outcomes [ 20 , 21 ]. Despite these numerous technological and organizational advances among others, the reductions in LOS have been inconsistently reported [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate preoperative identification of patients at risk for extended LOS and discharge to rehabilitation can provide substantial benefit, including more transparent communication on expected benefits and risks of surgery, postoperative planning, cost savings, preemptive administrative action, and optimization of modifiable patient risk factors 11–13. Many studies have determined significant risk factors in spine surgery, but most have been unable to create robust predictive models due to small cohort sizes and limited granularity of patient data 14,15. Of the reported predictive models, few capture the breadth of elective spinal cases, normally focusing on single types of procedures, diagnosis, or patient groups 16.…”
mentioning
confidence: 99%
“…[11][12][13] Many studies have determined significant risk factors in spine surgery, but most have been unable to create robust predictive models due to small cohort sizes and limited granularity of patient data. 14,15 Of the reported predictive models, few capture the breadth of elective spinal cases, normally focusing on single types of procedures, diagnosis, or patient groups. 16 A notable tool used for all types of surgeries is the American College of Surgeon's National Surgical Quality Improvement Program's (ACS NSQIP) online calculator, which utilizes 21 inputted preoperative factors to predict both LOS and discharge status.…”
mentioning
confidence: 99%